Race and rights : fighting slavery and prejudice in the Old Northwest, 1830-1870 - Weiner, Dana Elizabeth (Early American places, 2013)
In the Old Northwest from 1830 to 1870, a bold set of activists battled slavery and racial prejudice. This book is about their expansive efforts to eradicate southern slavery and its local influence in the contentious milieu of four new states carved out of the Northwest Territory: Illinois, Indiana, Michigan, and Ohio. While the Northwest Ordinance outlawed slavery in the region in 1787, in reality both it and racism continued to exert strong influence in the Old Northwest, as seen in the race-based limitations of civil liberties there. Indeed, these states comprised the central battleground over race and rights in antebellum America, in a time when race's social meaning was deeply infused into all aspects of Americans' lives, and when people struggled to establish political consensus. Antislavery and anti-prejudice activists from a range of institutional bases crossed racial lines as they battled to expand African American rights in this region. Whether they were antislavery lecturers, journalists, or African American leaders of the Black Convention Movement, women or men, they formed associations, wrote publicly to denounce their local racial climate, and gave controversial lectures. In the process, they discovered that they had to fight for their own right to advocate for others. This bracing new history by Dana Elizabeth Weiner is thus not only a history of activism, but also a history of how Old Northwest reformers understood the law and shaped new conceptions of justice and civil liberties. The newest addition to the Mellon-sponsored Early American Places Series, Race and Rights will be a much-welcomed contribution to the study of race and social activism in nineteenth-century America.